Constituição, ordenamento e conflitos normativos: Esboço de uma teoria analítica da ordenação normativa - Rocha, Joaquim Freitas (2022)
Sources of law are often presented from a hierarchical and pyramidal point of view, based on a traditional Kelsenian approach. However, in this book (doctoral thesis), I argue that contemporary legal orders shall be considered multilevel arrangements, comprising several types of legal links, relations and interactions (not only hierarchy, but also parity and self-reference).